Dampak Keputusan Merger pada Perbankan di Bursa Efek Indonesia - Dhani Ichsanuddin Nur (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
In the extremely competitive condition, a company is always expected to expand the strategy, in order to maintain its existent, or even develop and improve the performance.. Most business-joint in merger has been realized in external expansion. This research is to recognize the difference of company performance rank in finance ratio measurement, especially company in banking sector before and after merger.This research population was the whole banking company which are listed in BEI and do merger activity. Company performance in this research was measured in finance ratio, namely current ratio, quick ratio, total asset turn over, net profit margin, and return on assets. Each ratio was measured during 2 years periods before and 2 years after merger. To examine the differences between before and after merger, it was continued to do non parametric statistic test with Wilcoxon Sign Rank Test Analisys. The Analisys result showed that there was no significant difference in company performance for the period before and after merger. From this analisys, it could be concluded that merger was not affected to company performance in the term of liquidity rank, activity rank, and profitability rank. So it could be stated that the economy goal on the merger decision did not realize until the end of the second year.Keywords: Merger, company work, finance ratio